Productivity enhancement of rice based cropping system with fodder crops - Bindya B N (Department of Agronomy, College of Agriculture, 2019)
The study entitled “Productivity enhancement of rice based cropping system with fodder crops” was undertaken during 2017-2019 with the objectives to evaluate the suitability of different fodder crops in summer fallow of double cropped lowland rice fields under varying nitrogen regimes and to assess its residual effect on the succeeding virippu rice crop. The research work was carried out as two experiments, at the IFSRS, Karamana, Thiruvananthapuram. The experiment was laid out in RBD with 13 treatments replicated thrice, during summer 2017-18 and virippu 2018-19 seasons. In Experiment I, four fodder crops were raised during summer 2017-18 under varying nitrogen regimes. In Experiment II, first crop of rice (virippu) was raised in same plots during 2018-19 to assess the residual effect of the fodder crops on rice. In Experiment I, the treatments were T1 [fodder cowpea (FC) with 100 % recommended dose of nitrogen (RDN)], T2 (FC with 75 % RDN), T3 (FC with 50 % RDN), T4 [rice bean (RB) with 100 % RDN], T5 (RB with 75 % RDN), T6 ( RB with 50 % RDN), T7 [fodder maize (FM) with 100 % RDN)], T8 (FM with 75 % RDN), T9 (FM with 50 % RDN), T10 [(fodder sorghum (FS) with 100 % RDN)], T11 (FS with 75 % RDN), T12 (FS with 50 % RDN) and T13 (fallow during summer). The varieties of FC, RB, FM, FS and rice used were CO-9, Bidhan-2, African tall, CO FS-31 and Uma respectively. Regarding physiological parameters, at 20 days after sowing (DAS), LAI was significantly higher in FM, which was on par with FC (100% RDN). CGR (1 to 20 DAS) was significantly higher in FM. However, for 20 to 40 DAS, FC (100% RDN) was significantly higher, which was on par with FM (75% RDN) and FS (100 % RDN). NAR (1 to 20 DAS) was significantly higher in FS (100 % RDN) which was on par with other treatments of FS (75 and 50% RDN) and RB (50% RDN). NAR (20 to 40 DAS) was significantly higher in FS with 100% RDN which was comparable with FS with 50% RDN. SCMR was significantly higher in FC both at 20 and 40 DAS. Leaf: stem ratio was significantly higher in FC. FM produced significantly higher green fodder yield and dry fodder yield at all levels of nitrogen. Crude protein content was significantly more in FC (100 % RDN) and was comparable with FC (75 % RDN) and RB (100 % RDN). Crude fibre was significantly less in FC (100 % RDN) and RB (100 % RDN). At 20 DAS, weed smothering efficiency was significantly higher in RB (50% and 100 % RDN) which was on par with FC (100 and 75% RDN) and all the treatments of FM and FS. However, at 40 DAS, significantly higher weed smothering efficiency was in fodder cowpea (100 and 75% RDN). Net income was significantly higher in FM (50% RDN) which was on par with other treatments of FM (100 and 75% RDN) and FC (100 and 75% RDN). However, in case of B:C ratio, FC (100 and 75%) was significantly superior. The N balance sheet after summer crop was negative for all the treatments. In viruppu rice crop, except plant height, all the growth and yield attributes, net income and B: C ratio was observed to be unaffected by the preceding summer crops. The present study revealed that, among the different fodder crops tested, fodder maize performed better in the summer rice fallows with higher green fodder yield. However, with respect to net income it was comparable with fodder cowpea at 100 per cent and 75 per cent RDN. Fodder cowpea (100 and 75% RDN) recorded higher B: C ratio. Considering the shorter duration, better quality fodder and higher B: C ratio, fodder cowpea was assessed as the best fodder crop for the summer rice fallows. Yield, net income and B: C ratio of rice bean, fodder maize and fodder sorghum under varying doses of N were comparable, indicating the adequacy of 50 per cent RDN. Further, reducing the RDN for the summer crops did not have any adverse effect on the productivity and economics of the succeeding virippu rice.